Systemic vasculitis as a COVID -19 sequela in a patient with end-stage renal disease on chronic haemodialysis – A rare presentation - Niharika Mulpuri; Shankar Prasad Nagaraju; A Ravindra Prabhu; Indu R Rao; Dushyanth Babu Jasti (Indian Journal of Kidney Diseases)
COVID-19 is an ongoing global pandemic that has varied systemic manifestations. A 48-year-old male, with chronic kidney disease stage 5 on chronic haemodialysis and past history of COVID-19 three months ago, presented with urticarial skin rash and abdominal pain of seven days' duration. His immune workup ANA, ANCA, and Anti-GBM were negative. Punch biopsy of skin lesions showed immune complex vasculitis with C3, IgA, IgM, and fibrinogen deposition. His repeat throat and nasal swabs for COVID-19 were negative. After two days, he developed right axonal brachial plexopathy and diffuse alveolar hemorrhage. He was managed with intravenous methylprednisolone and five cycles of therapeutic plasma exchange. Thereafter, he was continued on oral prednisone and modified renal dose of oral cyclophosphamide. His regular maintenance hemodialysis sessions were continued. After two months, skin lesions resolved and limb weakness improved. Awareness of rare complications after COVID-19 recovery is essential for early recognition and appropriate management of these patients.